Sociodemographic and clinical characteristics of 1,234 individuals diagnosed with trichotillomania in the Swedish National Patient Register - Luis C. Farhat; Kayoko Isomura; Lorena Fernández de la Cruz; Anna Sidorchuk; Ralf Kuja-Halkola; Isabell Brikell; Zheng Chang; Brian M. D’Onofrio; Henrik Larsson; Paul Lichtenstein; David Mataix-Cols (Scientific Reports)
Abstract Trichotillomania is an understudied, underrecognized, and difficult-to-treat psychiatric disorder that affects about 1–2% of the population, predominantly women. This study aimed to characterize the sociodemographic and clinical characteristics of a Swedish cohort of individuals with a diagnosis of trichotillomania assigned in specialist services across the country. Through the Swedish National Patient Register, we identified all individuals with an ICD-10 diagnosis of trichotillomania between January 1st, 1997 and December 31st, 2020. The cohort included 1,234 individuals, with a median age at first diagnosis of 25 years (interquartile range, 16–35). Most individuals were female (85%) and single (82%). Most (79%) individuals had a comorbid psychiatric disorder diagnosed during the study period. Anxiety-related disorders (65%), depressive disorders (48%), and neurodevelopmental disorders (39%) were the most frequent co-occurring diagnoses. Most (72%) individuals were dispensed psychotropic medications during the period ranging from 12 months prior to and 12 months after the first trichotillomania diagnosis. Antidepressants (58%), hypnotics/sedatives (36%), and anxiolytics (31%) were the most frequently dispensed medications. Altogether, the characteristics of individuals diagnosed with trichotillomania in Swedish specialist services were similar to those reported in previous literature, opening the possibility of register-based research into this underdiagnosed and understudied condition.